Estimation of effective bulk composition—critical appraisal and a scanning electron microscope based approach. (26th January 2021) - Sharma, Jeev Jatan; Naik, Aditya; Pant, Naresh; Arora, Devsamridhi; Pandey, Mayuri; Singh, Preeti
Abstract : Pseudosections generated using the correctly estimated effective bulk composition (EBC), that is, the bulk of the closed metamorphic system that stays in chemical equilibrium are crucial in deciphering the PT history of a metamorphic terrain. A variety of tools are used by metamorphic petrologists to calculate the effective bulk of a sample, such as XRF bulk data, average bulk using point count analysis, and using X‐ray maps areal analysis, each with its own limitations. In this work, we demonstrate a scanning electron microscopy (SEM) based method to generate EBC, by analysing multiple grids of a thin section using area spectrum analysis tool and energy dispersive spectrometry (EDS) acquisition function of electron microscopes. The pseudosections generated using EBC estimated by SEM based method are tested over two pelitic granulites of east Antarctic shield and a medium‐grade metapelite from North Delhi Fold Belt of the Indian shield. The results are validated through thermobarometric estimations and are compared with pseudosections produced by using other bulk determination methods, such as XRF data and average bulk combining modal percentage with the mineral compositions. We propose that this method of calculating EBC is better compared to the other methods, as it allows the user to define the localized bulk of a particular domain, besides being a simpler and faster approach than other commonly used methods. Abstract : Pseudosections are generated using scanning electron microscope based effective bulk composition (EBC) for two pelitic granulites and one medium grade schist. The results are validated through conventional thermobarometric estimations and are compared to the pseudosections produced by using other bulk determination methods.